Karakteristik Kategori Adopter dalam Adopsi Inovasi Feed Additive Herbal untuk Ayam Pedaging (Adopter Category Characteristics on the Adoption of Herbal Feed Additive Inovation for Broiler) - Ayu Intan Sari; Suci Paramitasari Syahlani; F. Trisakti Haryadi (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
The aims of this research were to analyze the effect of characteristics of the farmer on the probability of adopter category difference, and to analyze the effect of farmer’s perception of innovation characteristics on the probability ofthe difference of adopter innovation of herbal feed additive for broiler. This research was conducted from August to October 2008, in the broiler farm at Karanganyar, Sragen, and Boyolali by using research based method of descriptiveanalysis. The respondents of the research were 34 farmers selected by using purposive convenience sampling. The data were analyzed using descriptive analysis, Mann-Whitney analysis, and logistic binominal regression analysis. Theresult of the research showed that there were differences in characteristics of the farmer between early and late adopter categories; they were age (p≤0.01), formal educational level (P≤0.01), cosmopolitness level (P≤0.01), and farmingexperience (P≤0.05). The result of logistic binominal regression test showed that age and formal education level were characteristics factor influencing the difference of adopter category significantly (P≤0.05), while the innovationcharacteristics consisted of relative advantage, complexity, and observability had significant effect (P≤0.05) on the adopter category difference. The conclusion of the research was that younger farmers, higher formal education level,longer experience, and higher level of active searching information seemed to have higher probability to become the early adopter. The farmers having higher perception of innovation characteristics, relative advantage and observability, and lower perception of complexity innovation characteristic tended to be early adopter.(Key words: Adopter category, Adoption, Herbal feed additive)